Interleukin-1β and tumor necrosis factor-α: reliable targets for protective therapies in Parkinson’s Disease? - Leal, María C.; Casabona, Juan C.; Puntel, Mariana; PITOSSI, FERNANDO (Frontiers in Cellular Neuroscience, 2013)
Neuroinflammation has received increased attention as a target for putative neuroprotective therapies in Parkinson´s Disease (PD). Two prototypic pro-inflammatory cytokines Interleukin-1beta (IL-1) and Tumor necrosis factor-alpha (TNF) have been implicated as main effectors of the functional consequences of neuroinflammation on neurodegeneration in PD models. In this review, we describe that the functional interaction between these cytokines in the brain differs from the periphery (e.g. their expression is not induced by each other) and present data showing predominantly a toxic effect of these cytokines when expressed at high doses and for a sustained period of time in the substantia nigra pars compacta (SN). In addition, we highlight opposite evidence showing protective effects of these two main cytokines when conditions of duration, amount of expression or state of activation of the target or neighboring cells are changed. Furthermore, we discuss these results in the frame of previous disappointing results from anti-TNF clinical trials against Multiple Sclerosis, another neurodegenerative disease with a clear neuroinflammatory component. In conclusion, we hypothesize that the available evidence suggests that the duration and dose of IL-1 or TNF expression is crucial to predict their functional effect on the SN. Since these parameters are not amenable for measurement in the SN of PD patients, we call for an in-depth analysis to identify downstream mediators that could be common to the toxic (and not the protective) effects of these cytokines in the SN. This strategy could spare the possible neuroprotective effect of these cytokines operative in the patient at the time of treatment, increasing the probability of efficacy in a clinical setting. Alternatively, receptor-specific agonists or antagonists could also provide a way to circumvent undesired effects of general anti-inflammatory or specific anti IL-1 or TNF therapies against PD.